Machine learning for multimodal healthcare data: first international workshop, ML4MHD 2023, Honolulu, Hawaii, USA, July 29, 2023 : proceedings - Maier, Andreas K.; Schnabel, Julia A.; Tiwari, Pallavi; Stegle, Oliver (Lecture notes in computer science, 2024)
This book constitutes the proceedings of the First International Workshop on Machine Learning for Multimodal Healthcare Date, ML4MHD 2023, held in Honolulu, Hawaii, USA, in July 2023. The 18 full papers presented were carefully reviewed and selected from 30 submissions. The workshop's primary objective was to bring together experts from diverse fields such as medicine, pathology, biology, and machine learning. With the aim to present novel methods and solutions that address healthcare challenges, especially those that arise from the complexity and heterogeneity of patient data
Literaturangaben
Keywords: Konferenzschrift